Computer-Assisted Instruction for Child Development: Evidence from an Educational Programme in Rural Zambia. Issue 7 (3rd July 2018) - Schling, Maja; Winters, Paul
Abstract: This paper examines whether computer-assisted instruction has a positive impact on the literacy and numeracy skills of early grade students. An educational intervention implemented in Zambia integrated technology into classroom activity in order to mitigate weaknesses in teaching skills and address specific unmet student needs. Using a difference-in-difference combined with inverse propensity weights, results show that students' numeracy and literacy skills are not significantly different from untreated community or government school students. At a third of the cost, the programme is the most cost-effective means of educating children in this poor region of Zambia.